The possessions : a novel - Murphy, Sara Flannery (Harper, an imprint of HarperCollinsPublishers, 2017)
"In an unnamed city, Edie works for the Elysian Society, a private service that allows grieving clients to reconnect with lost loved ones. She and her fellow workers, known as "bodies", wear the discarded belongings of the dead and swallow pills called lotuses to summon their spirits--numbing their own minds and losing themselves in the process. Edie has been with the company for five years, an unusual record. Her success is the result of careful detachment: she seeks refuge in the lotuses' anesthetic effects and avoids personal contact with her clients. But when Edie channels Sylvia, the deceased wife of Patrick Braddock, she becomes obsessed with the glamorous couple..."--